2018
DOI: 10.1111/chd.12583
|View full text |Cite
|
Sign up to set email alerts
|

A multinational observational investigation of illness perceptions and quality of life among patients with a Fontan circulation

Abstract: The Fontan sample's more negative perceptions of CHD were likely a reflection of life with a more complex defect. Illness perceptions appear to account for unique differences in QOL between groups of varying CHD complexity. Psychosocial screening and interventions may be important treatment components for patients with CHD, particularly those with Fontan circulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…People with a Fontan circulation or other forms of congenital heart disease (CHD) tend to see themselves as more well and less limited than objective evidence would suggest [7,8]. This is important because subjective perceptions are central to quality of life [9][10][11]. A meta-analysis exploring chronic childhood diseases and emotional outcomes showed a small increased risk of emotional difficulties that persisted into early adulthood [12].…”
Section: Challenges Of Having a Chronic Health Conditionmentioning
confidence: 99%
“…People with a Fontan circulation or other forms of congenital heart disease (CHD) tend to see themselves as more well and less limited than objective evidence would suggest [7,8]. This is important because subjective perceptions are central to quality of life [9][10][11]. A meta-analysis exploring chronic childhood diseases and emotional outcomes showed a small increased risk of emotional difficulties that persisted into early adulthood [12].…”
Section: Challenges Of Having a Chronic Health Conditionmentioning
confidence: 99%
“…Socio‐demographic data were collected by self‐reports and information on medical history was retrieved by chart reviews. Details on the methodology of APPROACH‐IS have been provided in a methods paper , and numerous papers have described findings obtained from this global sample or from patients from specific countries or regions .…”
Section: Approach‐ismentioning
confidence: 99%
“…Patients with Fontan circulation might experience an affected quality of life (37). Studies have reported a negatively affected quality of life (37)(38)(39)(40)(41)(42)(43) and reduced exercise performance even in patients without severe complications during surgical procedures and medical follow-ups (23,25,26,30). Also, it has been shown that patients with Fontan circulation have a lower quality of life compared with patients with less severe heart defects (38).…”
Section: Long-term Outcomementioning
confidence: 99%